Analisis Kesadaran Hukum Masyarakat Tionghoa Terhadap Pencatatan Perkawinan Di Kota Pontianak - Okrasiansah, Aldi; Hazilina, Hazilina; Lestari, Nina Niken (Faculty of Law, Universitas Muhammadiyah Pontianak, 2024)
Marriage Registration is very important in the legal system in Indonesia because it functions to provide certainty and legal protection for married couples and their children. However, in practice, not all Chinese people in Pontianak City prioritize ancestral customs and beliefs in carrying out marriages. This study aims to analyze the level of legal awareness of the Chinese community towards marriage registration and find out the legal impact if the marriage is not officially registered. The method used is empirical legal research with a qualitative approach. Primary data was obtained through questionnaires, interviews, and documentation, then analyzed descriptively. The results of the study show that although some Chinese people already understand the importance of marriage registration, there are still many who have not registered their marriages due to cultural reasons, processes that are considered complicated, and lack of socialization from the government. As a result, various legal problems arise such as unclear marital legal status, neglected civil rights of couples, and difficulties in taking care of documents needed by children. This research proposes the need for a collaborative approach between the government and customary/religious leaders in increasing legal awareness, as well as simplifying the registration administration process to make it more accessible to the public.